Genetic Research Trends in Caffeine Biosynthesis of Robusta Coffee (Coffea canephora) - Permatasari, Nindy; Sari, Sismita; Nurmayanti, Sri; Fauziah, Lu'lu' Kholidah; Sari, Resti Puspa Kartika; Hardani, Maisuri; Aliyah, Siti Hamidatul; Priyambodo, Priyambodo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Research on caffeine biosynthesis in Coffea canephora has expanded across multiple disciplines, yet its global genetic research trends remain insufficiently mapped. This study aimed to analyze the development and thematic structure of genetic research on caffeine biosynthesis in C. canephora using a bibliometric approach. Data were retrieved from the Scopus database through keyword-based sampling and filtered based on relevance to genetic and biosynthetic aspects. Bibliometric analyses were conducted to examine publication trends, authorship patterns, country contributions, and keyword co-occurrence networks. The results show a significant increase in publications since the early 2000s, with dominant contributions from the United States, Brazil, and China. Keyword mapping reveals four major research clusters, including plant metabolism, clinical and nutritional studies, experimental models, and genetic variability. However, studies explicitly focusing on the genetic regulation of caffeine biosynthesis, particularly involving N-methyltransferase genes, remain relatively limited compared to broader multidisciplinary themes.These findings indicate that caffeine research in C. canephora is highly interdisciplinary but still lacks a strong emphasis on genetic mechanisms, highlighting the need for more targeted molecular and genomic studies to support coffee improvement and functional trait development.